Mckelveyite group minerals – Part 4: Alicewilsonite-(YLa), Na2Sr2YLa(CO3)6 ⋅ 3H2O, a new lanthanum-dominant species from the Paratoo mine, Australia - I. Lykova; R. Rowe; G. Poirier; H. Friis; K. Helwig (European Journal of Mineralogy, 2024)
The new mckelveyite group mineral, alicewilsonite-(YLa), Na2Sr2YLa(CO3)6 ⋅ 3H2O, was found together with kamphaugite-(Y), paratooite-(Y), bastnäsite-(La), and decrespignyite-(Y) coating along fractures in dolomite at the Paratoo copper mine, South Australia, Australia. It occurs as pale pink to colourless pseudohexagonal tabular crystals up to 150 µm in size. The streak is white; the lustre is vitreous. The mineral has no cleavage. Dcalc is 3.37 g cm−3. Alicewilsonite-(YLa) is optically biaxial (−), α = 1.556(2), β= 1.582(2), γ= 1.592(2), 2V (meas.) = 60(2)°, 2V (calc.) = 63° (589 nm). The IR spectrum is reported. The composition (wt %, average of seven analyses) is Na2O 7.43, CaO 2.00, SrO 18.43, BaO 1.64, Y2O3 9.59, La2O3 11.74, Pr2O3 1.29, Nd2O3 5.74, Sm2O3 0.44, Eu2O3 0.09, Gd2O3 0.95, Dy2O3 1.15, Ho2O3 0.25, Er2O3 0.89, Yb2O3 0.29, CO2 29.78, H2O 6.18, total 97.88. The empirical formula calculated on the basis of six cations with 3 H2O molecules is as follows: Na2.10Ca0.31Sr1.56Ba0.10Y0.74La0.63Pr0.07 Nd0.30Sm0.03Eu0.01Gd0.04Dy0.05Ho0.01Er0.04 Yb0.01(CO3)5.92(H2O)3. The mineral is triclinic, P1, a= 8.9839(2), b= 8.9728(3), c= 6.7441(2) Å, α= 102.812(2)°, β= 116.424(2)°, γ= 60.128(2)°, and V= 422.17(2) Å3 and Z= 1. The strongest reflections of the powder X-ray diffraction pattern [d,Å(I)(hkl)] are 6.03(43)(001), 4.355(100)(1<mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="58b89df6a568f22bd126fa17cec2e421"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00001.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00001.png"/></svg:svg>0, <mover accent="true">2‾</mover><mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="dac27974c69484527cbc2bfef3831989"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00002.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00002.png"/></svg:svg>1, 120), 4.020(30)(<mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="d15d55faba11fbb2897545ff3996eeb3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00003.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00003.png"/></svg:svg>11, 210, <mover accent="true">1‾</mover><mover accent="true">2‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="0fef6d37cc7bc75076f80ec64be63d90"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00004.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00004.png"/></svg:svg>1), 3.188(29)(<mspace width="0.125em" linebreak="nobreak"/><mover accent="true">2‾</mover><mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="6bd1d55d919bea431e51f1f31693b08e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00005.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00005.png"/></svg:svg>2, 1<mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="7c5dbfb675e56fab2aad9c252ef1545f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00006.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00006.png"/></svg:svg>1, 121), 2.819(96)(002, <mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="93134270f7cadb8b0aec402ea46c3d8f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00007.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00007.png"/></svg:svg>12, 211, <mover accent="true">1‾</mover><mover accent="true">2‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="12713b639de16434216e93ad67c3f7a0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00008.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00008.png"/></svg:svg>2), 2.592(40)(<mover accent="true">3‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="9fa9e8dba581cad1e86c88af822ec50f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00009.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00009.png"/></svg:svg>01, 030, <mover accent="true">3‾</mover><mover accent="true">3‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="5c05b18c4d219fbf187e34b20c271026"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00010.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00010.png"/></svg:svg>1), 2.228(33)(<mover accent="true">2‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="9b9d4b7da08f01ac1b26235632266996"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00011.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00011.png"/></svg:svg>21, <mover accent="true">4‾</mover><mover accent="true">2‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="a728b56d26a8df380354fb4e8b7bc12b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00012.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00012.png"/></svg:svg>1, <mover accent="true">2‾</mover><mover accent="true">4‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="437febe734386a4124c8e0b63df27bf7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00013.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00013.png"/></svg:svg>1). 2.011(36)(<mover accent="true">2‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="4c640149faf94bed07b44fa2ccacc6f7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00014.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00014.png"/></svg:svg>22, 003, 420, <mover accent="true">2‾</mover><mover accent="true">4‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="ad2beb7dab081b5772b140f06afa4615"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00015.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00015.png"/></svg:svg>2), 1.9671(32)(<mover accent="true">3‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="5da2cd8f0b343e467ab7093d639dc1d0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00016.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00016.png"/></svg:svg>03, 301, 0<mover accent="true">3‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="c6472df561403b9adee12ede6c55cbc1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00017.svg" width="8pt" height="13pt" src="ejm-36-301-2024-ie00017.png"/></svg:svg>2, 032, <mover accent="true">3‾</mover><mover accent="true">3‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="0302da968ec247513629afa45878d94a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-301-2024-ie00018.svg" width="14pt" height="13pt" src="ejm-36-301-2024-ie00018.png"/></svg:svg>3, 331). The crystal structure was solved and refined from single-crystal X-ray diffraction data (R1= 0.058).